2011
DOI: 10.1590/s0066-782x2011005000092
|View full text |Cite
|
Sign up to set email alerts
|

Proteína C Reativa pré-operatória prediz infecção respiratória após cirurgia de revascularização miocárdica

Abstract: Background: Increased levels of high-sensitive C-reactive protein (hsCRP) in the preoperative evaluation for coronary artery bypass graft surgery (CABG) have been associated to poor outcomes in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In a study conducted by Agda Mezzomo, it was indicated that hsCRP levels higher than 3 mg/dl can be used to predict respiratory infections associated with old age and increased mechanical ventilation (>24 h) and that preoperative hsCRP cannot predict cardiovascular events such as atrial arrhythmias (atrial fibrillation) or death. [12] In a study carried out by Biancari et al ., it was detected that patient candidates for coronary bypass surgery with CPB and preoperative serum concentration of CRP≥1.0 mg/ dl would carry a higher risk of overall, low cardiac output syndrome, and postoperative cardiac death. [13] Preoperative serum concentration of CRP≥1.0 mg/dL was significantly more frequent among patients with a history of myocardial infarction and low left ventricular ejection fraction in patients undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Agda Mezzomo, it was indicated that hsCRP levels higher than 3 mg/dl can be used to predict respiratory infections associated with old age and increased mechanical ventilation (>24 h) and that preoperative hsCRP cannot predict cardiovascular events such as atrial arrhythmias (atrial fibrillation) or death. [12] In a study carried out by Biancari et al ., it was detected that patient candidates for coronary bypass surgery with CPB and preoperative serum concentration of CRP≥1.0 mg/ dl would carry a higher risk of overall, low cardiac output syndrome, and postoperative cardiac death. [13] Preoperative serum concentration of CRP≥1.0 mg/dL was significantly more frequent among patients with a history of myocardial infarction and low left ventricular ejection fraction in patients undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…CRP levels in that study were unrelated to pneumonia risk, though the CRP assay used in that study was not a newer high-sensitivity assay such as the one we used, so their CRP data may have been compromised to some degree. Two other studies of patients undergoing cardiac surgery also showed that elevated preoperative CRP levels were associated with increased postoperative respiratory infection risk [27], [28].…”
Section: Discussionmentioning
confidence: 94%
“…However, specificity of this risk model seems to be poor and prevents implementation of preventive strategies. Another cohort study from Brazil in 331 patients with a rate of 16% for postoperative pneumonia comes to the conclusion that preoperative level of highly sensitive C-reactive protein (CRP) >3 mg/l is an independent predictor for postoperative respiratory infection [28]. However, specificity is also problematic with this approach, as CRP is not only increased in pulmonary infections, but also in a variety of comorbidities.…”
Section: Discussionmentioning
confidence: 99%